Correlations between microbial diversity, monomeric phenols, and biological parameters during spontaneous fermentation of Cabernet Sauvignon grapes obtained from rain-shelter cultivation. (15th December 2022) - Huang, Rong; Yu, Hongfei; Dong, Chao; Shen, Lei; Qin, Yi; Liu, Yanlin; Jiang, Jiao; Song, Yuyang
Abstract: This study aimed to evaluate the effect of rain-shelter on microbial diversity in spontaneous fermentation of Cabernet Sauvignon wines, and the correlations of core microbial taxa with biological parameters and monomeric phenols, with an open-field mode as the control. Firstly, rain-shelter increased the contents of 2.6% alcohol, 6.8% glycerol, 10.3% malic acid and 20.3% catechins in resulting wines, respectively ( P < 0.05). As fermentation advanced, bacterial diversity decreased and then increased, while fungal diversity decreased ( P < 0.05), regardless of cultivation. Besides, significant correlations were identified between Acetobacter, Pseudonocardia, Leuconostoc, Starmerella, Aspergillus and Saccharomyces and biological properties and monomeric phenols. Finally, the functions of bacterial genes were predicted to be primarily related to carbohydrate and amino acid metabolisms; fungi were more abundant in glycolytic pathway, and coenzyme A biosynthesis fatty acid elongation pathway. Overall, this information provides important insights into the succession and metabolism of indigenous microbes mediated by rain-shelter. Graphical abstract: Image 1 Highlights: Rain-shelter increased the alcohol, glycerol, malic acid and catechin levels of the final wine. The variations in biological parameters were concentrated in MF and EF, with monomeric phenols at EF. OPLS-DA model identified glycerol, lactic acid and benzoic acid as differential metabolites. Microbial community succession during spontaneous fermentation of wine under rain-shelter mode was confirmed. Relationships between biological parameters, monomeric phenols and microbial communities were established.